The correlation between age and hormonal concentration in infertile females: a cross-sectional study - Chamanshaikh, Shahista A.; Patil, Archana R.; Patil, Rajendra S. (International Journal of Research in Medical Sciences, 2026)
Background: Infertility is a global health issue with significant social and emotional consequences, affecting approximately 48 million couples and 186 million individuals worldwide. Female infertility commonly results from abnormalities of the uterus, fallopian tubes, ovaries, or endocrine disturbances that disrupt reproductive hormones. Methods: This cross-sectional study included 110 infertile women who attended the department of obstetrics and gynaecology after at least one year of marriage without conception. Participants were categorized into three age groups: 20–25 years, 26–35 years, and ≥36 years. Results: Serum follicle-stimulating hormone (FSH) and luteinizing hormone (LH) levels showed a significant positive correlation with age (FSH: r=0.44, p<0.0001; LH: r=0.35, p=0.0002), with the highest values observed in women aged ≥36 years, indicating declining ovarian reserve. In contrast, anti-Müllerian hormone (AMH) levels demonstrated a significant negative correlation with age (r=-0.30, p=0.0015), reflecting reduced fertility potential in older women. Thyroid-stimulating hormone (TSH) levels also increased significantly with age (r=0.50, p<0.0001), suggesting a higher prevalence of thyroid dysfunction, which may contribute to ovulatory disturbances and menstrual irregularities. Conclusions: Advancing age is associated with increased FSH, LH, and TSH levels and decreased AMH levels, highlighting the impact of aging on reproductive function. Comprehensive hormonal evaluation, particularly in women aged ≥36 years, is essential for understanding infertility and optimizing fertility management strategies.